Evaluation of relationship of intuitive eating and eating awareness with body mass index and anthropometric measurements in adults - Dağ, Ayhan; Özören, Aliye; Baran, Özlem (Progress in Nutrition, 2023)
Objective: This study was conducted to assess effects of intuitive eating and eating awareness on body mass index (BMI) and anthropometric measurements (nutritional habits, food choices and amount of consumption) in adults. Material and method: This study was conducted with adult residents from Lefkoşa, North Cyprus Turkish Republic between September, 2020 and November, 2020. Overall, 386 subjects were recruited to the study, including 247 women and 139 men. The demographic characteristics were recorded using a data sheet and anthropometric measurements were performed in all subjects. The Intuitive Eating Scale-2 (IES-2) was used to assess level of intuitive eating behavior while the Eating Awareness Scale-30 (EAS-30) was used to assess eating awareness. Findings: It was found that there were significant, negative correlations between IES-2 scores and body weight and BMI in female subjects (p<0.05). It was also detected that there were significant, negative correlations between IES-2 scores and body weight and BMI in the whole study population (p<0.05). The IES-2 scores were found as 3.62±0.54 in underweight subjects, 3.55±0.42 in normal subjects, 3.39±0.44 in overweight subjects and 3.27±0.40 in obese subjects. In our subjects, the body weight and BMI were decreased by increasing IES-2 scores. It was found that there was a significant difference in IES-2 total scores across BMI classes (p<0.05). In general, it was detected that there were significant, negative correlations between EAS-30 and body weight and BMI in our subjects (p<0.05). The body weight and BMI were decreased by increasing EAS-30 scores. Conclusion: The increased intuitive eating and eating awareness are associated with low body mass index. It can be recommended to use intuitive eating and eating awareness approach to achieve or maintain ideal body weight.